Creating a teenager’s imagination - Dzikarienė, V. (Psichologija, 1963)
This article examines certain features of school-aged children’s imagination. Based on the creative writings tasks of kids in 5th-8th grade, collected throughout the experiment, teen imagination dependence on the general characteristics of this period of development are revealed. Imagination activity largely focuses on "unusual events" in which the author of the work itself actively participates. The material shows that teenagers, unlike younger students, are able to not only recreate a given text, but also operate using their imaginative experience in a given situation. They often create dynamic, living, decorated, immediate, emotional experiences and synthetic images. It speaks of sufficient mental potential for creative imagination development during adolescence. The analysis of creative writing also found that teen imagination is underdeveloped, ala diagrammatic manifestation, one-sided stories, failure to combine separate images into a single synthetic image. The native language and literature program are not running sufficiently at eight year schools along these lines, and also teachers do not make use of all opportunities to help develop creative imagination papers